Relationship Between the Marketing Mix (7Ps) and Consumers’ Decision to Use Suki A Restaurant at Mega Bangna Shopping Center - ศรีฟ้า, วัชราภรณ์; วงษ์เล็ก, ภูษิตย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were 1) to examine the marketing mix factors (7Ps) influencing consumers' decisions to use the services of Suki A Restaurant at Mega Bangna shopping center 2) to examine the decision-making process of consumers using the services of Suki A Restaurant at Mega Bangna shopping center and 3) to analyze the relationship between the marketing mix factors (7Ps) and consumers' decisions to use the services of Suki A Restaurant at Mega Bangna shopping center. The sample consisted of 126 customers who had decided to use the services of Suki A restaurant at Mega Bangna Shopping Center. The samples were selected using accidental sampling. The research instruments used was a questionnaire with the content validity (IOC) of r = 0.67, p < 1.00 and a reliability coefficient of 0.99. The data were analyzed using descriptive statistics, including percentage, mean, and standard deviation. Pearson’s correlation coefficient was employed to test the research hypotheses at the 0.01 level of statistical significance.          The research result revealed that 1) The marketing mix factors (7Ps) influencing consumers' decisions to use the services of Suki A Restaurant at Mega Bangna shopping center, both overall and for each individual item, were at the highest level (Mean = 4.52), 2) The consumers' decisions to use the services of Suki A Restaurant at Mega Bangna shopping center were at a high level (Mean = 4.48) and 3) There was a positive correlation between the marketing mix factors (7Ps) and consumers' decisions to use the services of Suki A Restaurant at Mega Bangna shopping center at a moderate level (r=0.55), which was statistically significance at the 0.01 level.